Psychiatric morbidity and clinical correlates in substance dependence: A study from a tertiary care center in Sitapur - Yogi Rana; Abhishek Pathak; Manish Singh; Vishesh Yadav; Rahul Singh (Asian Journal of Medical Sciences, 2025)
Background: Dependence syndrome due to psychoactive substance use is a significant public health concern, impacting individuals, families, and society. Aimed to investigate the clinical correlates and psychiatric morbidity among individuals with substance use disorders at a tertiary care center in Sitapur. Aims and Objectives: The aim and objective of this study were to evaluate the clinical correlates and psychiatric morbidity in patients with dependence syndrome due to psychoactive substance use at a tertiary care center. Materials and Methods: This descriptive cross-sectional study was conducted over 18 months, including 390 patients aged 18–60 years, all diagnosed with dependence syndrome due to psychoactive substance use according to the International Classification of Diseases-10 criteria. Patients visiting psychiatry outpatient department/inpatient department/consultation-liaison psychiatry cases were assessed using semi-structured pro forma and standardized tools, including the alcohol, smoking, and substance involvement screening test. Results: The study included 390 patients, predominantly male (94.10%), with a significant portion aged 31–50 years. Most participants were from lower socioeconomic backgrounds, with alcohol, cannabis, and mixed substances being the most used. A high prevalence of psychiatric comorbidities was found, with 60.25% exhibiting mood and anxiety disorders. The severity of psychiatric comorbidities varied across different risk levels. Conclusions: The study underscores the need for gender-sensitive prevention strategies, targeted interventions for middle-aged adults, and comprehensive care models addressing both substance use and psychiatric comorbidities. Integrated treatment approaches, public health campaigns, and robust support systems are essential to improve health outcomes.